Enhancement of Power System Stability Using Fuzzy Logic Controller - Tejaswita Khobaragade; Amol Barve (Institute of Advanced Engineering and Science, 2012)
This Dissertation includes work on the development of a fuzzy logic power system stabilizer to enhance the damping of generator oscillations In order to accomplish a stability enhancement. Speed deviation (Am) and acceleration (Aw) of the rotor synchronous generator were taken as the input to the fuzzy logic controller. These variables take significant effects on damping the generator shaft mechanical oscillations. The stabilizing signals were computed using the fuzzy membership function depending on these variables. The performance of the fuzzy logic power system stabilizer was compared with the conventional power system stabilizer and without power system stabilizer. To achieve good damping characteristics over a wide range of operating conditions, speed deviation and acceleration of a synchronous machine are chosen as the input. Signal to the stabilizers. The stabilizing signal is determined from certain rules for rule-based power system stabilizer. For fuzzy logic based power system stabilizer, the supplementary stabilizing signal is determined according to the fuzzy membership function depending on the speed and acceleration states of the generator. The simulation result shows that the proposed fuzzy logic based power system stabilizer is superior to rule-based stabilizer due to its lower computation burden and robust performance.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.2127